A fixed carbohydrate:protein ratio ≤ 1.8 on an energy basis consumed in the context of an energy‐restricted diet and reduction of body weight: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (13th June 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Marks and Spencer PLC, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of the United Kingdom, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to a CHO:P ratio ≤ 1.8 on an energy basis in the context of an energy‐restricted diet and body weight. The Panel considers that the food/constituent that is the subject of the health claim is sufficiently characterised. The Panel also considers that reduction of body weight in the context of an energy‐restricted diet is a beneficial physiological effect. The target population proposed by the applicant is 'adults between the ages of 18 and 70 years with excess body weight'. No conclusions could be drawn from two unpublished studies investigating the effect of ready‐to‐eat meals with a CHO:P ratio ≤ 1.8 on body weight. The remaining 14 human intervention studies investigated the effect of diets targeting a CHO:P ratio ≤ 1.8 as compared to diets targeting a CHO:P ratio ≥ 3.0 on overweight and obese adults in the context of energy restriction. Four out of seven studies lasting < 12 weeks reported an effect of a CHO:P ratio ≤ 1.8 on body weight in overweight/obese subjects, whereas no significant effect was observed in six out of the seven studies lasting 12 weeks or more. The Panel considers that these studies do not provide evidence for a sustained effect of the food/constituent on body weight. The Panel concludes that a cause and effect relationship has not been established between the consumption of a fixed CHO:P ratio ≤ 1.8 on an energy basis consumed in the context of an energy‐restricted diet and reduction of body weight.